2024
DOI: 10.1007/s00227-023-04368-0
|View full text |Cite
|
Sign up to set email alerts
|

Implications of changing Caribbean coral reefs on Diadema antillarum larvae settlement

Tom Wijers,
Britt van Herpen,
Djan Mattijssen
et al.

Abstract: Tropical western Atlantic reefs have gradually shifted from being dominated by corals to being mainly covered by macroalgae. The mass-mortality of the sea urchin Diadema antillarum in the 80s and the slow to non-existent recovery exacerbated this shift. Chemical cues associated with these reefs are expected to have shifted too with potential negative effects on larval recruitment, possibly limiting recovery of important species like D. antillarum. In this study, we tested the effects of naturally derived biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…In our study, only 'La Jaca' exhibited su cient levels of recruitment to allow us to detect a clear pattern of avoidance by early D. africanum recruits in treatments containing Lobophora schneideri. A similar result was recently observed in laboratory assays performed by Wijers et al (2024), who also found lower settlement rates of the Western Atlantic sibling species Diadema antillarum on Lobophora variegata tiles in comparison with other algae treatments such as CCA, Sargassum uitans, and Padina pavonica. These observations can be explained by previous studies showing that the widespread algae genus Lobophora can produce multiple secondary metabolites, such as 2,4-dibromophenol (Vieira et al 2017), which has been found to inhibit the metamorphosis of several species of sea urchins (Agatsuma et al 2008;Li et al 2011).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, only 'La Jaca' exhibited su cient levels of recruitment to allow us to detect a clear pattern of avoidance by early D. africanum recruits in treatments containing Lobophora schneideri. A similar result was recently observed in laboratory assays performed by Wijers et al (2024), who also found lower settlement rates of the Western Atlantic sibling species Diadema antillarum on Lobophora variegata tiles in comparison with other algae treatments such as CCA, Sargassum uitans, and Padina pavonica. These observations can be explained by previous studies showing that the widespread algae genus Lobophora can produce multiple secondary metabolites, such as 2,4-dibromophenol (Vieira et al 2017), which has been found to inhibit the metamorphosis of several species of sea urchins (Agatsuma et al 2008;Li et al 2011).…”
Section: Resultssupporting
confidence: 89%
“…This settlement phase encompasses all the processes necessary for the transition from pelagic to benthic life, including substrate selection and metamorphosis. Certain algal species, such as CCAs, are able to have a great in uence on the sea urchin settlement phase, by providing competent larvae with appropriate cues to initiate settlement (Pearce and Scheibling, 1990;Huggett et al 2006;Swanson et al 2006;Dworjanyn and Pirozzi, 2008;Pilnick et al 2023;Wijers et al 2024). Conversely, although lesser studied, some algal species are able to constrain sea urchin settlement success due to the release of toxic compounds (Norris and Fernical, 1982;Agatsuma et al 2008;Li et al 2011;Wijers et al 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many species of sea urchins respond to bare substrate or those with new biofilms as cues for settlement (Bak, 1985;Pearce and Scheibling, 1991;Rahim et al, 2004;Williams et al, 2011), but the spatiotemporal patterns of settlement by D. antillarum vary appreciably among locations (Bak, 1985;Miller et al, 2009;Vermeij et al, 2010;Williams et al, 2010Williams et al, , 2011Feehan et al, 2019;Maldonado-Sańchez et al, 2019;Hylkema et al, 2022a). Recent laboratory experiments by Pilnick et al (2023) and Wijers et al (2024) revealed a lack of settlement by competent D. antillarum larvae exposed to a sterile seawater control, but settlement rates increased to ~50% in response to two types of calcareous macroalgae (Pilnick et al, 2023;Wijers et al, 2024) and to natural biofilms (Wijers et al, 2024). If settlement hotspots are identified it is possible to collect high numbers of D. antillarum settlers during certain months of the year (Williams et al, 2010(Williams et al, , 2011Hylkema et al, 2022a;Klokman and Hylkema, 2024).…”
Section: Urchinsmentioning
confidence: 99%